2014
DOI: 10.1002/jcph.203
|View full text |Cite
|
Sign up to set email alerts
|

A FIM Study to Assess Safety and Exposure of Inhaled Single Doses of AP301—A Specific ENaC Channel Activator for the Treatment of Acute Lung Injury

Abstract: AP301 is an activator of ENaC-mediated Na+ uptake for the treatment of pulmonary permeability edema in acute respiratory distress syndrome (ARDS). The purpose of this “first-in-man” study was to examine local and systemic safety and systemic exposure of ascending single doses of AP301, when inhaled by healthy male subjects. In a double-blind, placebo-controlled study, 48 healthy male subjects were randomized to 6 ascending dose groups (single doses up to 120 mg) of 8 subjects each (3:1 randomization of AP301: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…The lung is vulnerable to damage and a role in SIRS (3). ALI commonly leads to severe hypoxemia, thereby leading to the dysfunction of other organs and potentially multiple organ failure (4). Therefore, ALI is the initial stage in the whole pathological process of SIRS, which results in organ dysfunction and subsequent multiple organ failure.…”
Section: Introductionmentioning
confidence: 99%
“…The lung is vulnerable to damage and a role in SIRS (3). ALI commonly leads to severe hypoxemia, thereby leading to the dysfunction of other organs and potentially multiple organ failure (4). Therefore, ALI is the initial stage in the whole pathological process of SIRS, which results in organ dysfunction and subsequent multiple organ failure.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Support for this experimental direction is provided by the finding that inhaled TIP peptide (a.k.a. AP301 and solnatide) was recently found to be safe in a phase 1 clinical trial in volunteers 27 and displayed promising activities on lung function in 2 phase 2a clinical trials in patients with acute lung injury 28 and after lung transplantation. 29 Initially, we assessed whether TIP peptide treatment could blunt pathology and restore renal function during the course of acute nephritis in a murine NTN model and whether this was primarily mediated by renal or systemic activities of the TIP peptide.…”
mentioning
confidence: 99%
“…The TIP peptide has been shown to activate ALC in several animal models of hydrostatic and permeability edema (21,(29)(30)(31). In a recently performed, placebocontrolled, double-blind Phase I clinical trial, TIP peptide (also named AP301) was observed not to induce serious adverse effects upon inhalation (32) Bacterial and viral toxins have been shown to induce significant changes in ENaC P o and/or expression, leading to impaired ALC (33)(34)(35)(36). It is therefore of high clinical relevance to identify novel mechanisms that increase ENaC function during pulmonary edema associated with ARDS and pneumonia, for which no standard therapy exists to date.…”
mentioning
confidence: 99%